Coronary artery calcification in middle‐aged women with premature ovarian insufficiency. (23rd May 2019) - Gunning, Marlise N.; Meun, Cindy; van Rijn, Bas B.; Maas, Angela H. E. M.; Benschop, Laura; Franx, Arie; Boersma, Eric; Budde, Ricardo P. J.; Appelman, Yolande; Lambalk, Cornelis B.; Eijkemans, Marinus J. C.; Velthuis, Birgitta K.; et al.
Abstract: Objective: Women with premature ovarian insufficiency (POI) enter menopause before age 40. Early menopause was associated with increased risk for coronary artery disease (CAD), death from cardiovascular disease and all‐cause mortality. We compared the prevalence of CAD between middle‐aged women on average 10 years following the initial POI diagnosis, with a population‐based cohort. Design: Cross‐sectional case‐control study. Participants: Women from two Dutch University Medical Centers above 45 years of age previously diagnosed with POI (n = 98) were selected and compared with age‐ and race‐matched controls from the Multi‐Ethnic Study of Atherosclerosis (MESA). Measurements: The primary outcome was detectable coronary artery calcium (CAC) determined by coronary computed tomography (CCT). Results: Women with POI had significantly higher blood pressure, cholesterol and glucose, despite lower BMI compared to controls. Similar proportions of detectable CAC (CAC score >0 Agatston Units) were observed in women with POI and controls (POI n = 16 (16%), controls n = 52 (18%), P = 0.40 and P adj = 0.93). In women with POI separately, we were not able to identify associations between CVD risk factors and CAC. The following CVD risk factors in controls were positively associated with CAC: age, diabetes mellitus, hypertension and LDL cholesterol. HRT use was negatively associated with CAC in controls. Conclusions: The presence of CAC did not differ significantly in women with POI around 50 years of age, compared to an age‐ and race‐matched control group. We observe no increased calcified coronary disease in POI patients, despite the presence of unfavourable cardiovascular risk factors in these women.